2019
DOI: 10.1007/s11883-019-0798-2
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Stroke: an Update

Abstract: Purpose of the review: Maternal morbidity and mortality is rising in the United States, and maternal stroke is a major contributor. Here, we review the epidemiology, risk factors and current recommendations for diagnosis and acute treatment of ischemic and hemorrhagic stroke during pregnancy and postpartum, focusing on recent evidence. Recent findings:The incidence of maternal stroke has risen in recent years, possibly due to increasing rates of hypertensive disorders of pregnancy. The risk of maternal stroke … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 115 publications
(106 reference statements)
0
33
0
1
Order By: Relevance
“…Metabolic processes (e.g., basal metabolic rate, protein usage and storage, triglyceride synthesis, hemodynamic changes) become altered during pregnancy to provide an optimal supply of glucose and protein to mothers and fetuses [ 1 ]. These alterations may extend to the 4th trimester (12 weeks post-delivery) or later in life with increases in the risks for complications, such as maternal stroke or delivery of macrosomic infants [ 9 ]. A continuum of care from preconception to the 4th trimester for women who are overweight or obese is essential [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Metabolic processes (e.g., basal metabolic rate, protein usage and storage, triglyceride synthesis, hemodynamic changes) become altered during pregnancy to provide an optimal supply of glucose and protein to mothers and fetuses [ 1 ]. These alterations may extend to the 4th trimester (12 weeks post-delivery) or later in life with increases in the risks for complications, such as maternal stroke or delivery of macrosomic infants [ 9 ]. A continuum of care from preconception to the 4th trimester for women who are overweight or obese is essential [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, another risk factor for female subjects is the peripartum period and early postpartum period. 20,21 In fact, it is called maternal stroke. 21 During these periods, the risk for ischemic stroke increase.…”
Section: Discussionmentioning
confidence: 99%
“…20,21 In fact, it is called maternal stroke. 21 During these periods, the risk for ischemic stroke increase. 20 Conversely, it has been reported that lower levels of education, a lower income, and higher area deprivation were associated with increased risk of stroke among both men and women equally.…”
Section: Discussionmentioning
confidence: 99%
“…Recent clinical studies demonstrate a significantly elevated risk for cerebral ischemia and stroke in the PP period ( Kittner et al, 1996 ; Skidmore et al, 2001 ; Simon et al, 2015 ). Several stroke risk factors were identified, including hypertensive disorders of pregnancy, older age, infections, migraine and pre-pregnancy cardiovascular disease ( Evans et al, 2011 ; Hovsepian et al, 2014 ; Leffert et al, 2015 ; Cunningham and LaMarca, 2018 ; Zambrano and Miller, 2019 ).…”
Section: Discussionmentioning
confidence: 99%